The role of yellow lupin (Lupinus luteus) in the decline affecting oak agroforestry ecosystems - SERRANO, M S; FERNÁNDEZ-REBOLLO, P; DE VITA, P; CARBONERO, M D; SÁNCHEZ, M E (Forest Pathology, 2011)
Phytophthora cinnamomi is a soilborne pathogen causing root rot in Mediterranean Quercus species growing in dehesa rangeland ecosystems. Recently, it has been reported causing wilting and death of Lupinus luteus (yellow lupin), a spontaneous plant in southern Spain rangelands, but also frequently sowed for livestock grazing. In soils artiﬁcially infested with P. cinnamomi chlamydospores and planted with diﬀerent cultivars of yellow lupin, a signiﬁcant increase in the density of propagules was detected in comparison with the initial levels of inoculum and with the infested but not planted soil (control). In oak-rangelands in which yellow lupine was planted, isolation and counting of colonies of P. cinnamomi from soil samples have shown the ability of this plant to maintain or even increase the inoculum density and thus facilitate the infection of trees. Results suggested that cultivation of yellow lupin in oak-rangeland ecosystems should be avoided whether oak trees are aﬀected by root disease caused by P. cinnamomi or not. This leguminous plant can act as an inoculum reservoir or even enhance inoculum soil levels available for oak root infections, exacerbating the oak decline severity in the region.
Keywords: inoculum density (voyant); Lupinus luteus; Oak decline; phytophthora cinnamomi; root disease